Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik Pada Kantor Desa Keranji Mancal Kecamatan Sengah Temila Kabupaten Landak - Adi Mursalin; Merlinda (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This thesis entitled "Analysis of Community Satisfaction with Public Services at the Keranji Mancal Village Office, Sengah Temila District, Landak Regency" (Based on the Community Satisfaction Index). The purpose of this study was to determine the level of community satisfaction with services at the Keranji Mancal Village Office. In the research method, the writer uses the survey method. According to Ali Maksum (2012: 95. "Survey research is an effort to solve research problems by using certain methods that can direct activities to a specific goal, by collecting data through observation, interviews, questionnaires, documentation. In this study the method used was for analysis refers to the Community Satisfaction Index (IKM. The results of the study show that community satisfaction with public services at the Keranji Mancal Village Office, Sengah Temila District, Landak Regency is good. The author provides some suggestions and input to the Keranji Mancal Village Office, hopefully it can be useful and useful so that it can improve services for the better.